Assessing the State of Population Health by Age-adjusted Life Expectancies - Feldmann, U.; Mehnert, R. F. (Methods of Information in Medicine, 2006)
Objectives: A gain in life expectancy of a population is commonly interpreted as an effect of improved health care. After the reunion of Germany in 1990 life expectancy at birth grew extremely in the new federal states. Within one decade after reunion the new federal states had a gain in life expectancy of about five years while the gain in the old federal states was only about two years.Methods: It has been widely argued that this phenomenon is caused by an obviously improved public health service and environmental protection or even by an increased social status in the new federal states. On the other hand, the median population age grew rapidly in the new federal states, caused by a dramatic reduction of the birth rate as well as a high emigration rate of young people. Using real time series for three selected federal states and for the total Federal Republic of Germany, it is derived that most of the gain in life expectancy is explained by population ageing.Results: An elementary probabilistic procedure is proposed allowing for estimating the amount in life expectancy not attributable to population ageing.Conclusions: The age-adjusted life expectancy can be regarded as an unbiased measure of a populations’ state of health that stays comparable both over time and across countries.
Keywords: Age at death; Bayes’ theorem; fertility; health care; life expectancy; life tables; migration; population ageing; state of health of populations